An Assessment Of Occupants’ Satisfaction On The Property Management Service Quality: A Study On Mixeduse Building - Tum, Choo Yoong (2022)
The growth in population and land scarcity in the city lead to the increase in vertical buildings and the development of mixed-use buildings become more instead of single-function buildings such as residential buildings and commercial buildings to support the population and the infrastructure. However, this building also brings several problems to property management due to the complexity of the building. Property management need to understand the current needs and wants from the people to maintain the service quality and satisfaction. Hence the researcher is eager to discover dimensions of service quality for property management should concentrate on those that can aid to improve occupants’ satisfaction. This study aims to determine the factors of service quality that influence occupant satisfaction in a mixed-use building. Content analysis is used to identify the service quality aspects of tangible, reliability, responsiveness, assurance, and empathy. A correlation between occupant satisfaction and building service quality variables is also examined in this study. The reliability of measurement models was determined using internal consistency reliability and indicator reliability analysis by checking on the composite reliability and indicator loading. The validity of measurement models determined using average variance extracted (AVE) to determine convergent validity, cross loading, Heterotrait–Monotrait Ratio (HTMT) and the Fornell-Larcken Criterion to determine discriminant validity. Assessment of the structural models using variance inflation factor (VIF), r-square, f-square and q-square. A total of 500 respondents were collected using the convenience and snowball sampling method through online questionnaires, a structural equation model (SEM) analysis was used to assess the relationships between the independent and dependent variables. Next, this research evaluates factors of service quality that influence the occupants’ satisfaction the most in the mixed-use building. The empirical findings from this research found that there are four out of five independent variables were showed a significant relationship with the dependent variable which are tangibles, reliability, assurance and empathy. Although the responsiveness dimension shows no substantial relationship to the occupants’ satisfaction in this context, however, it does not represent that this variable is irrelevant, as numerous researchers have proved. In this study, the tangibles dimension is the factor of service quality influencing the occupants’ satisfaction the most in the mixed-use buildings followed by empathy, assurance and reliability. The property management need put more effort to enhance the tangibles dimension to keep occupants satisfy their service. The dimensions highlighted in this study, as well as those yet to be explored and investigated by future researchers must be considered. These findings of the research also can provide awareness to the current property management company and staff to enhance their service quality through implementing corrective action and prioritizing the work based on its importance which ultimately increases the occupants’ satisfaction.